Rhoeo discolor (Trandescantia spathacea) a textile dye source - Buena, Mylene Vergara; Elumba, Patricia Santos (2002.)
The rhoeo discolor leaf is a potential source of textile dye. From the initial run of the Philippine Textile Research Institute on the extraction of rhoeo discolor leaves, further study of the affinity of the extract applied to natural fibers in the form of fabrics such as jusi, cotton and silk was performed. Aqueous extraction was used and a red violet to purple extract was obtained. Alum and copper sulfate were used as mordant with 2%, 4%, 5%, and 6% w/v concentration to the pretreated fabrics. The pH of the red violet aqueous extract was 5.7 indicating its acidity and addition of glacial acetic acid (Technical Grade) led to a more acidic extract with a red orange color. Likewise, soda ash was added to a fraction of the extract to come up with basic dye extract which is dark green in color. The three extracts were used as dyes to mordanted jusi and different colors were obtained. Jusi mordanted with 2% copper sulfate exhibited the most intense shade of the colors. The aqueous dye extract was applied to cotton, jusi and silk mordanted with 5% alum and copper sulfate. Jusi and silk showed the best dyeing results. Samples mordanted with copper sulfate gave a darker shade of color compared to those mordanted with alum which showed negligible intensities of color with varying alum concentration. The three dye extracts were characterized using a Sequoia Turner Single Beam UV Vis spectrophotometer and pH meter.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Dye plants; Rhoeo; Dyes and dyeing